Recurrent interphalangial dislocation of the great toe (A case report) - Karakurt, Lokman; Yilmaz, Erhan (My University, 2002)
Interphalangial dislocation of the great toe is not common and rewiew of the literature was revealed no previous reports of the recurrent dislocation of this joint. We determined a recurrent dislocation of the interphalangieal joint of the great toe in a 33 year-old women who admitted our clinical department with a complain of great toe pain while walking. Pain was originated from osteoarthritis of the 1.MP joint and we thougth that, if the interphalangial instability may be prevented, the toe pain may be relieved. So, we did planned operative intervention to interphalangial instability. Intraoperatively, we did not found cartilage defect, but determined lateral capsular defect and lateral kollateral ligament complete rupture and remnant capsule was plicated to the lateral sheath of the extensor hallucis longus tendon. After the 7 months follow-up period postoperatively, result was excellent.
Ayak 1. Parmak i?nterfalangi?al eklem tekrarlayan çiki?i (Olgu sunumu)
Keywords: Great toe; Instability; Interphalangial Joint; Recurrent Dislocation